THE URGENCY OF TECHNOLOGY-BASED EDUCATION FOR PRIMARY SCHOOL IN INDONESIA - Djusmalinar Djusmalinar; Fajar Dwi Mukti (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2022)
The rapid development of technology and the need for Primary School-age children in educational innovation to compete in the modern era provide a paradigm that needs to be studied more deeply on how urgent technology is in Primary School. Based on this, the researchers analyzed the urgency of technology-based education for Primary School in Indonesia. The method in this research is a literature review that examines the importance of the topics discussed and compares the results with findings in other studies on the same issue. Based on the research results, the urgency of technology-based education in Primary School is as follows. (1) The characteristics of Primary School-age children who like exciting things and like varied learning enable technology as a concrete solution, (2) Technology can facilitate educators in giving assignments to students in gathering information from various sources, including from the internet (3) Technology can minimize internal weaknesses, (4) Technology-based education can reach all learning areas anytime and anywhere so that the role of technology in learning in Primary School can facilitate the formation of collaborative relationships and build meaning in easier contexts. Technology-based education for Primary School has three main functions used in learning activities: (1) Technology functions as a tool. In this case, technology is used as a tool for educators to convey learning information in the form of knowledge to students to make it easier for them to understand the material. (2) Technology functions as science. In this case, technology is part of a scientific discipline that students must master. (3) Technology functions as materials and tools for learning (literacy). In this case, technology is interpreted as a learning material and a tool to master a computer-assisted competency. In this case, the position of technology is no different from that of a teacher who functions as a facilitator, motivator, transmitter, and evaluator